Community Sanctification of Forgiveness - Bell, Christopher (Journal of psychology and theology, 2014)
Previous research has yielded mixed findings regarding the relationship between religion/spirituality (R/S) and forgiveness. This study examined the degree to which victims view forgiveness as spiritually valuable within their R/S community. We developed the Community Sanctification of Forgiveness (CSF) scale to assess this construct. We divided the sample (N = 307) into two subsamples (n = 157; n = 150, respectively) in order to conduct exploratory and confirmatory factor analyses. We then examined whether CSF was related to forgiveness in the combined sample (N = 307). We found that religious commitment moderated the relationship between CSF and forgiveness, such that greater community expectations for forgiveness were positively related to forgiveness only for individuals high on religious commitment. Implications for R/S, forgiveness, and the measurement of these constructs are discussed.